VATS thoracoscopic decortication for empyema thoracic. A retrospective experience and analysis of 162 cases - Farhan Ahmad Majeed; Sohail Saqib Chatha; Usama Zafar; Ahmad Ali; Nabeela Farhan; Ahmad Raza (Journal of the Pakistan Medical Association, 2020)
Objective: To analyse the experience of empyema thoracis management using video-assisted thoracoscopic surgery. Method: The retrospective study was conducted at the Combined Military Hospitals, Rawalpindi and Lahore, Pakistan, and comprised data of empyema thoracis cases who underwent thoracoscopic decortications by the same consultant surgeon between January 2009 and 2018. Uniportal or multiportal video-assisted thoracoscopic decortications was done. Histopathology and microbiological sampling were done in all cases. Results: of the 162 cases, 114(70.4%) were done on males and 48(29.6%) on females. The overall mean age was 44±16.37 years. Three ports were utilised in 58(36%) patients. Hospital stay of 122(75.3%) patients was <5 days post-procedure. Post-thoracotomy neuralgia occurred in 19(11.7%) patients, while 9(5.5%) had surgical site infection. Overall complications were 30(18.5%). There was no mortality. Conclusion: Video-assisted thoracoscopic decortications was found to be a safe, effective and efficient procedure. Key Words: VATS, Decortication, Empyema thoracis. Continuous...